2019
DOI: 10.1063/1.5095475
|View full text |Cite
|
Sign up to set email alerts
|

A study of VUV emission and the extracted electron-ion ratio in hydrogen and deuterium plasmas of a filament-driven H−/D− ion source

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…[20] the authors concluded that: "The volume production of H − is enhanced by gas mixing because the cold electron density near the extraction increases as heavier ions bring cold electrons through the magnetic filter to the low-energy plasma chamber". The given explanation contradicts the conclusion by Komppula et al arguing that volume production of D − ions in a multicusp ion source is limited by the diffusion of the heavier isotope across the transverse filter field [21]. Thus, alternative explanations for the H − beam current enhancement by the Xe admixture should be sought.…”
Section: On the Possibility Of Ion Pair Production In Plasma Ion Sourcesmentioning
confidence: 63%
“…[20] the authors concluded that: "The volume production of H − is enhanced by gas mixing because the cold electron density near the extraction increases as heavier ions bring cold electrons through the magnetic filter to the low-energy plasma chamber". The given explanation contradicts the conclusion by Komppula et al arguing that volume production of D − ions in a multicusp ion source is limited by the diffusion of the heavier isotope across the transverse filter field [21]. Thus, alternative explanations for the H − beam current enhancement by the Xe admixture should be sought.…”
Section: On the Possibility Of Ion Pair Production In Plasma Ion Sourcesmentioning
confidence: 63%
“…Neither the spectra nor the volumetric rates of ionization, excitation, production of high vibrational states, and dissociation between the two isotopes showed any significant difference. It is therefore suggested that in this source, the observed difference between the H − and D − production through dissociative electron attachment (DEA) is attributed most likely to the difference in the diffusion properties of hydrogen and deuterium [27].…”
Section: Introductionmentioning
confidence: 99%